2018
DOI: 10.3389/fmicb.2018.01120
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Falciparum Malaria and Emergence of Severe Dengue: An Independent or Interdependent Phenomenon?

Abstract: The global malaria burden, including falciparum malaria, has been reduced by 50% since 2000, though less so in Sub-Saharan Africa. Regional malaria elimination campaigns beginning in the 1940s, up-scaled in the 1950s, succeeded in the 1970s in eliminating malaria from Europe, North America, the Caribbean (except Haiti), and parts of Asia and South- and Central America. Dengue has grown dramatically throughout the pantropical regions since the 1950s, first in Southeast Asia in the form of large-scale epidemics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 99 publications
(119 reference statements)
0
6
2
Order By: Relevance
“…Our study also reported significantly higher odds of malaria infection among patients with malaria mono-infection than acute dengue virus co-infection. This could be due to the inter-species cross-protection of dengue virus infection against malaria [11]. Our finding does not corroborate the reports of Kotepui et al 2019 [47] and Kotepui et al 2020 [53].…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Our study also reported significantly higher odds of malaria infection among patients with malaria mono-infection than acute dengue virus co-infection. This could be due to the inter-species cross-protection of dengue virus infection against malaria [11]. Our finding does not corroborate the reports of Kotepui et al 2019 [47] and Kotepui et al 2020 [53].…”
Section: Discussioncontrasting
confidence: 97%
“…This could be due to the inter-species cross-protection of dengue virus infection against malaria. 11 Our finding does not corroborate the reports of Kotepui et al 2019 53 and Kotepui et al 2020 59 . Kotepui et al 2019 showed significantly lower odds of co-infection while Kotepui et al 2020 reported no notable difference in co-infection due to acute dengue compared to malaria mono-infection.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Cross-reactivity of both dengue IgM and IgG, however, is known to exist with malaria and leptospirosis; there seems to be cross-reactivity with other flaviviruses as well, such as Zika and Japanese encephalitis [ [13] , [14] , [15] ]. The cross-reactivity with flaviviruses is expected as dengue virus and other flaviviruses share a large degree of structural and sequence homology; the same phenomenon occurring with malaria is speculated to result from the elicitation of cross-reactive antibodies or other immune responses that infer cross-protection, or at least partial cross-protection, against symptomatic and severe dengue [ 15 ].…”
Section: Discussionmentioning
confidence: 99%